Exploring out-of-focus camera calibration for improved UAV survey accuracy (2024)
Calibrating large-range vision systems like UAV cameras is a complex task that often involves costly setups and the potential for errors due to inaccuracies in target fabrication. Traditional UAV surveying software typically estimates camera parameters alongside ground control points, but this method may lack optimal accuracy. Our study explores an alternative: using out-of-focus camera calibration to improve the reliability and accuracy of drone cameras for surveying. In our approach, the UAV camera is positioned several meters away from a low-cost target to ensure focus. We then calibrate the intrinsic camera parameters using an out-of-focus small calibration target, fixing these parameters before flight. For evaluation, we compare this method against the standard approach of estimating UAV camera parameters with survey imagery. Preliminary results suggest that this out-of-focus method offers a reliable and accurate solution for UAV surveying applications.